Lysine specific demethylase 1 inactivation enhances differentiation and promotes cytotoxic response when combined with all-trans retinoic acid in acute myeloid leukemia across subtypes - Smitheman, K.N.; Severson, T.M.; Rajapurkar, S.R.; McCabe, M.T.; Karpinich, N.; Foley, J.; Pappalardi, M.B.; Hughes, A.; Halsey, W.; Thomas, E.; Traini, C.; Federowicz, K.E.; et al. (FERRATA STORTI FOUNDATION, 2019)
Lysine specific demethylase 1 (LSD1) is a histone modifying enzyme that suppresses gene expression through demethylation of lysine 4 on histone H3. The anti-tumor activity of GSK2879552 and GSK-LSD1, potent, selective irreversible inactivators of LSD1, has previously been described. Inhibition of LSD1 results in a cytostatic growth inhibitory effect in a range of acute myeloid leukemia cell lines. To enhance the therapeutic potential of LSD1 inhibition in this disease setting, a combination of LSD1 inhibition and all-trans retinoic acid was explored. All-trans retinoic acid is currently approved for use in acute promyelocytic leukemia in which it promotes differentiation of abnormal blast cells into normal white blood cells. Combined treatment with all-trans retinoic acid and GSK2879552 results in synergistic effects on cell proliferation, markers of differentiation, and, most importantly, cytotoxicity. Ultimately the combination potential for LSD1 inhibition and ATRA will require validation in acute myeloid leukemia patients, and clinical studies to assess this are currently underway.